Upaya Baitul Maal Wat Tamwil (BMT) NU Dalam Membangun Kepercayaan Dan Loyalitas Nasabah (Studi Kasus: BMT NU Cabang Grujugan Bondowoso) - Ela Masruroh; Sugiono Sugiono (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the BMT NU branch of grujugan in building trust in customer loyalty. In line with the increasingly high level of competition between financial institutions, every company must strive to further develop its competitive capabilities. One of the difficulties faced by BMT NU is building customer trust, It can be said that not all individuals have the trust and responsibility that can be make customers loyal and loyal. In conducting data collection to be able to produce the necessary research data. Researchers used 2 (two) data collection techniques in the form of interviews and observations. The results show that trust is the glue that strengthens customers to believe and vice versa. If trust has arisen, then the step is to establish cooperation It will be easier so that it will benefit both parties. Trust customers have an impact in creating customer loyalty. Customers will be loyal or loyal on a product or service if the customer already has high trust in the product or service.